The fourth turning eaudiobook What the cycles of history tell us about america's next rendezvous with destiny. - Strauss, William (Books on Tape, 2023)
Now available as an unabridged recording for the first time NATIONAL BESTSELLER • Discover the game-changing theory of the cycles of history and what past generations can teach us about living through times of upheaval—with deep insights into the roles that Boomers, Generation X, and Millennials have to play.   First comes a High, a period of confident expansion. Next comes an Awakening, a time of spiritual exploration and rebellion. Then comes an Unraveling, in which individualism triumphs over crumbling institutions. Last comes a Crisis—the Fourth Turning—when society passes through a great and perilous gate in history. William Strauss and Neil Howe will change the way you see the world—and your place in it. With blazing originality, The Fourth Turning illuminates the past, explains the present, and reimagines the future. Most remarkably, it offers an utterly persuasive prophecy about how America’s past will predict what comes next.   Strauss and Howe base this vision on a provocative theory of American history. The authors look back five hundred years and uncover a distinct pattern: Modern history moves in cycles, each one lasting about the length of a long human life, each composed of four twenty-year eras—or “turnings”—that comprise history’s seasonal rhythm of growth, maturation, entropy, and rebirth. Illustrating this cycle through a brilliant analysis of the post–World War II period, The Fourth Turning offers bold predictions about how all of us can prepare, individually and collectively, for this rendezvous with destiny.